2018
DOI: 10.4093/dmj.2018.0055
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence for an Obesity Paradox in Type 2 Diabetes Mellitus

Abstract: Although overweight/obesity is a major risk factor for the development of type 2 diabetes mellitus, there is increasing evidence that overweight or obese patients with type 2 diabetes mellitus experience lower mortality compared with patients of normal weight. This paradoxical finding, known as the “obesity paradox,” occurs in other chronic diseases, and in type 2 diabetes mellitus is particularly perplexing given that lifestyle intervention with one goal being weight reduction is an important feature of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 52 publications
3
83
0
1
Order By: Relevance
“…This finding may be justified with the paradox of obesity which was recently reported in some studies. 37,38 In older adults, overweight may particularly be accompanied by a lower risk of all-cause and cardiovascular motility. 37 Furthermore, among type 2 diabetic patients, the U-shaped association of BMI with all-cause mortality with adjusted age, sex, systolic blood pressure, diastolic blood pressure, fasting plasma glucose, total cholesterol, triglyceride, smoking, and diabetes duration has been observed which showed that overweight participants had a significantly lower hazard ratio of mortality than other BMI groups.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be justified with the paradox of obesity which was recently reported in some studies. 37,38 In older adults, overweight may particularly be accompanied by a lower risk of all-cause and cardiovascular motility. 37 Furthermore, among type 2 diabetic patients, the U-shaped association of BMI with all-cause mortality with adjusted age, sex, systolic blood pressure, diastolic blood pressure, fasting plasma glucose, total cholesterol, triglyceride, smoking, and diabetes duration has been observed which showed that overweight participants had a significantly lower hazard ratio of mortality than other BMI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) is widely used to assess health status based on weight and height. In general, higher BMI (overweight and/or obesity) is an indicator of increased risk of developing a range of conditions, including metabolic disorders, such as type 2 diabetes mellitus (T2DM) (Bays, Chapman & Grandy, 2007;Han & Boyko, 2018). Weight fluctuation is commonly associated with dietary consumption, and increasing food intake overtime, can lead to gaining weight.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of thyroid cancer has been increasing throughout the world during the last few decades [30][31][32][33]. During the same time period, the prevalence of obesity has dramatically increased and has become a major public health issue worldwide [34,35]. In addition to the widespread use of high-resolution imaging tools, changes in lifestyle and environmental factors are considered contributing factors to an increase in the incidence of thyroid cancer [33,36].…”
Section: Discussionmentioning
confidence: 99%